Domain Systems originating in the fields - Franciskovic Ingunza, Millitza (2016)
It varied the number of works dealing with this topic and generally confusion is caused by the number of systems and the arbitrary use of the names that are identified, which has caused describing under the same name different systems or the same system various labels. Therefore in this paper we reduce the theme of the original domain to the next question: Who originally owned mineral deposits? Without pretend clarify the picture  explaining  each of the systems because it would lead to an investigation of historical character that is not our goal.